PORTRAYING LEECH’S MODEL OF POLITENESS IN CAPITAL R RAKE BRIDGERTON SEASON 2 - Sunarti Desrieny Tambunan (Jurnal Sosial Humaniora dan Pendidikan, 2022)
This research portrays about the implementation of maxims of politeness in the first episode of Bridgerton Season 2, entitled Capital R Rake. The aim is finding out the maxims of politeness. The method used is qualitative descriptive method. The results shows that there are 15 data of Tact Maxim, 5 data of Generosity Maxim, 27 data of Approbation Maxim, 18 data of Modesty Maxim, 14 data of Agreement Maxim, and 7 data of Sympathy Maxim. The most maxim that appears is Approbation Maxim. The least maxim that appears in the movie is Generosity.